Relationship between popularity and the likely efficacy: an observational study based on a random selection on top-ranked physical activity apps. Issue 11 (14th November 2019) - Bondaronek, Paulina; Slee, April; Hamilton, Fiona L; Murray, Elizabeth
Abstract : Objectives: To explore the relationship between popularity of mobile application (apps) for physical activity (PA) and their likely efficacy. The primary objective was to assess the association between app popularity (indicated by user ratings) and likely efficacy (indicated by the number of Behaviour Change Techniques (BCT) present). The secondary objective was to assess the relationship between user ratings and those BCTs that have been shown to be effective in increasing PA. Design: Observational study. Methods: 400 top-ranked free and paid apps from iTunes and Google Play stores were screened, and were included if the primary behaviour targeted was PA and they had stand-alone functionality. The outcome variable of user rating was dichotomised into high (4, 5 stars) or low (1, 2, 3 stars) rating. Setting: iTunes and Google Play app stores. Participants: No individual participants but the study used user-led rating system in the app store. Primary and secondary outcome measures: BCTs and user rating. Results: Of 400 apps, 156 were eligible and 65 were randomly selected, downloaded and assessed by two reviewers. There was no relationship overall between star ratings and the number of BCTs present, nor between star ratings and the presence of BCTs known to be effective in increasing PA. App store was strongly associated with star ratings, with lower likelihood of finding 4 or 5 stars in iTunes compared with Google Play (OR 0.74, 95% CI 0.73 to 0.76, p<0.001). Conclusions: The findings of this study suggest that popularity does not necessarily imply the likelihood of effectiveness. Hence, public health impact is unlikely to be achieved by allowing market forces to 'prescribe' what is used by the public.